Communicating the culture of consumerism spatiality of SM Mall, Baguio City, Philippines - Sta Maria-Abalos, Cecilia Fe L. (2011)
An alternative view of looking at space as a communication apparatus that constructs the culture of consumerism, the study takes a postmodern lens and begins its discourses on the city, consumerism, SM as an exemplar space, and Baguio local's display of consumerism. Soja's Trialectics of Spatiality as a frame of reference, emphasized the third space which unfolded the narratives of the perceived, conceived and lived spatiality of SM Baguio. Using the city map and photographs as cultural texts, the research draws into the discussion the notions of the city and space as ideations and actualizations that create and re-create the culture of consumerism.
Keywords: SM Mall, Baguio City